On the Ionization and Ion Transmission Efficiencies of Different ESI-MS Interfaces - Cox, Jonathan T. (J Am Soc Mass Spectrom, 2014)
The achievable sensitivity of electrospray ionization mass spectrometry (ESI-MS) is largely determined by the ionization efficiency in the ESI source and ion transmission efficiency through the ESI-MS interface. These performance characteristics are difficult to evaluate and compare across multiple platforms as it is difficult to correlate electrical current measurements to actual analyte ions reaching the detector of a mass spectrometer. We present an effective method to evaluate the overall ion utilization efficiency of an ESI-MS interface by measuring the total gas phase ion current transmitted through the interface and correlating it to the observed ion abundance measured in the corresponding mass spectrum. Using this method we systematically studied the ion transmission and ionization efficiencies of different ESI-MS interface configurations, including a single emitter/single inlet capillary, single emitter/multi-inlet capillary, and a subambient pressure ionization with nanoelectrospray (SPIN) MS interface with a single emitter and an emitter array, respectively. Our experimental results indicate that the overall ion utilization efficiency of SPIN-MS interface configurations exceeds that of the inlet capillary-based ESI-MS interface configurations.